STUDY OF FISHING PORT FACILITIES REQUIREMENT’S INJARING HALUS VILLAGE SECANGGANG SUB DISTRICT LANGKAT DISTRICT OFNORTH SUMATERA - Rumiyati '; Jonny Zain; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Abstract This research was conducted on October 2016 in the village of Jaring Smooth, Secanggang, Langkat, North Sumatra Province, aimed to find out type and size / capacity fishing ports facilities need. used a survey method. The result of the research indicated that the length of loading docks required is 40.43 meters, 3.61 meter length unloading dock. Extensive pool is needed 9643.3 meter2 port, port depth of the pool 1,98 meter and turning basin 452.16 meter2 well as an extensive fish auction hall 6.5 meter2. Ie go to sea capacity needs supplies amounting to fuel tank 410 liters, 355 liters fresh water tank and capacity 459 kilograms ice plants. From the results obtained that fishing ports be recommended is of type D is referred to Fish Landing Base (PPI) or Fish Landing Place.Keywords : Facility Type, Size Facilities, Fishing Port